Isolation and Identification of Gram Positive Cocci Bacterial Pathogens from Sappurative Otitis Media Infections - Al-Hamadany, Weam Saad (The Iraqi Journal of Veterinary Medicine, 2013)
Otitis Media (OM) is a common disease. It represents a serious problem mainly after winter outbreaks of respiratory tract infections (RTI); its consequences are hearing weakness; or even loss in adults and problems in speech in children. Gram-positive Cocci bacteria are among the causative pathogens. This study concerned with suppurative otitis media caused by gram-positive Cocci bacteria; either as pure culture or mixed with other pathogens. A total of 60 ear swabs were collected from Ear, Nose and Throat Department outpatients in AL-Nuaman hospital in Baghdad and cultured to isolate and identify the most common causative bacterial pathogen among gram positive Cocci. Staphylococcus aureus was the most common isolated bacteria (81.6%) representing (53.3%) as pure culture and (28.3%) as mixed. Streptococcus pneumonia was the second isolated pathogen (18.3%) representing (8.3%) as pure culture and (10%) as mixed. The mixed culture represented other pathogens like gram-negative bacteria and fungi.